Desarrollo de una empresa comercializadora de café de haba en la ciudad de Machala. - Carrión Elizalde, Yuri Elizabeth (2017)
The present project of entrepreneurship has as objective, the creation of a business idea, the development of a Marketing Company of Coffee of Haba in the city of Machala. With the collection of data obtained from the methodology used; Qualitative (survey and interview) has been able to have a base in terms of the perception of the product of bean coffee in the citizens Machaleños referring to the survey and in the interview the survey was directly with the product, interviewed the managers of the Wholesalers reporting important results on the competition. The basic marketing fundamentals put into practice in the development of this work have allowed us to verify how feasible and profitable it is, with a market analysis and strategies put forward. The Macroentorno was investigated where the different factors intervene; Taking into account the laws established in our country Ecuador, the economic stability it presents at present, the existing technological tools, customs and tastes of individuals. The microenvironment was also examined, dealing with points such as those who provide the bean fruit, potential customers, analyzing the substitute article for bean coffee, and ending with the barriers that prevent its commercialization. Organic coffee production; Is a proposal that is different from the rest of classic competitors; With a 100% natural good made from dried beans, roasted and ground, taking advantage that the product has an excellent reception for its nutritional benefits. Analyzing the process and quality control not only of the product, but also of the Company itself, must be efficient and efficient, produce with quality and warmth in the services associated with the product it provides. The characteristics of bean coffee were defined, detailing the design of the container, its brand and its logo. The appropriate route or route of distribution will be made by the Retailer channel that comprises from the producer to the wholesaler and retailer ending with the final consumer. On the other hand the strategies elaborated are in order to obtain benefits for the company, having a good position within the market at local, national and possibly international level. The study of technical, financial, operational, environmental and social feasibility are useful tools in a project; That have been developed to have real results and that these steps are key to the success of the creation of the Marketing Company within a market sated by strong competitors. To finish, the process of this new idea of entrepreneurship will be applied within a local market where there are competitors with brands already fully positioned, this is where the bean coffee marketing company enters with a new product, putting into practice all the strategies Of Marketing built, all methodology outlined in the present scheme, learning from the competition their failures and their tactics, to achieve recognition, the expected income from consumers and potential customers.